Isolation improvement of discrete PIN diode switch using square dumbbell Defected Ground Structure - Abdul Hadi, M.H. (Institute of Electrical and Electronics Engineers Inc., 2015)
The potential application of Defected Ground Structure (DGS) for isolation improvement of series discrete PIN diode switch is proposed in this paper. A square dumbbell DGS was selected for this application where it was connected in parallel with a single series discrete PIN diode. By realizing the circuit using FR4 substrate, the simulated and measured result clearly show that the isolation of the series discrete PIN diode during OFF state can be improved by square dumbbell DGS. By demonstrating it in 1.5 GHz frequency band, more than 30 dB isolation can be achieved if compared to single series discrete PIN diode without DGS. Â© 2014 IEEE.